2000
DOI: 10.1111/j.1447-0756.2000.tb01203.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Labour and Delivery on Plasma Hepatic Enzymes in the Newborn

Abstract: The reference values are comparable to those published for Caucasian populations. There are moderate elevations in LDH and AST associated with the onset of labour and changes in acid-base status.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 4 publications
0
6
0
Order By: Relevance
“…We also consider the finding that LDH has a slightly higher predictive value in the big group with normal saturation, temperature and capillary refill as very interesting, as it means that plasma LDH increases earlier than these clinical signs in a significant proportion of the patients. Previous (12,13) and on‐going research have established reference ranges for LDH in term newborn infants, whereas good reference studies in the preterm group are still scarce. In the group of term newborn infants, we found that the best cut‐off values for prediction of need of NICU (group A) in our study, is exceeding the upper normal LDH limit from the literature, which is in the range of 500–700 U/L.…”
Section: Discussionmentioning
confidence: 99%
“…We also consider the finding that LDH has a slightly higher predictive value in the big group with normal saturation, temperature and capillary refill as very interesting, as it means that plasma LDH increases earlier than these clinical signs in a significant proportion of the patients. Previous (12,13) and on‐going research have established reference ranges for LDH in term newborn infants, whereas good reference studies in the preterm group are still scarce. In the group of term newborn infants, we found that the best cut‐off values for prediction of need of NICU (group A) in our study, is exceeding the upper normal LDH limit from the literature, which is in the range of 500–700 U/L.…”
Section: Discussionmentioning
confidence: 99%
“…Cord blood is easily accessible immediately after birth, but reference values have only been reported for a limited number of healthy infants in which the means of excluding factors that might affect LDH in plasma are not described [3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…Both LDH and AST in normal newborns were inversely related to pH and BE, which suggested that the more significant the hypoxia, the higher the LDH and AST levels. 7 Gunes showed increasing elevation of LDH with an increasing degree of perinatal asphyxia. Their mean AST on day 1 was higher in the mild (84 U/L), moderate (160 U/L), and severe asphyxia (227 U/L) groups compared to their control (70 U/L) group.…”
Section: Discussionmentioning
confidence: 92%
“…8 For healthy non-asphyxiated newborns, normal LDH levels are between 330-700 IU⁄ L in the first 24 hours, and between 320-600 IU/L at 72 hours. 7,8 Because perinatal hypoxia results in plasma LDH elevation postpartum, it is important to identify infants with some degree of perinatal hypoxia to appropriately interpret their postnatal LDH levels. We used the term "perinatal hypoxia" to denote some degree of oxygen deficiency, if insufficient to satisfy the "perinatal asphyxia" criteria defined earlier.…”
Section: Discussionmentioning
confidence: 99%